2020
DOI: 10.1002/ana.25797
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Core Features in Four Developmental Encephalopathies in the Rett Natural History Study

Abstract: Objective Rett syndrome, CDKL5‐deficiency disorder, FOXG1 disorder, and MECP2 duplication disorder are developmental encephalopathies with shared and distinct features. Although they are historically linked, no direct comparison has been performed. The first head‐to‐head comparison of clinical features in these conditions is presented. Methods Comprehensive clinical information was collected from 793 individuals enrolled in the Rett and Rett‐Related Disorders Natural History Study. Clinical features including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 42 publications
3
32
0
Order By: Relevance
“…Most studies resulting from our search concerned epileptiform abnormalities/seizures in RTT ( Figure 1 , Table 1 ). Seizures of various semiology were described, with the most common being generalized seizures, tonic-clonic seizures and complex partial seizures [ 41 , 42 , 43 , 44 , 45 ]. Reports on the prevalence of epilepsy in patients with RTT ranged between 50 and 90%, and about 30–50% of cases were drug-resistant [ 41 , 44 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies resulting from our search concerned epileptiform abnormalities/seizures in RTT ( Figure 1 , Table 1 ). Seizures of various semiology were described, with the most common being generalized seizures, tonic-clonic seizures and complex partial seizures [ 41 , 42 , 43 , 44 , 45 ]. Reports on the prevalence of epilepsy in patients with RTT ranged between 50 and 90%, and about 30–50% of cases were drug-resistant [ 41 , 44 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, causal relationships between seizures and developmental trajectory of RTT disorder remains unclear. For example, a recent large-scale study of 793 individuals reported that there were no significant associations between age of developmental regression and age of seizure onset in patients with RTT or in patients with so-called RTT-like disorders [ 42 ]. Thus, findings of the above correlative nature do not ascertain whether the epilepsy plays a crucial role in deteriorated cognitive abilities in RTT, or if it alternatively reflects the more severe underlying pathophysiology [ 105 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our prior studies reveal considerable variability in severity of many symptom domains within MDS including ambulation, hand function, and non‐verbal communication (Ramocki, Tavyev, & Peters, 2010) that could be related to gene duplication size and content (Peters et al, 2019). Developmental regression occurs in approximately half of the population with highly variable age of onset (Cutri‐French et al, 2020; Peters et al, 2013a). A comprehensive picture of the natural history and severity of MDS is needed as disease‐modifying therapies may be possible, as demonstrated by the recent report of phenotypic reversal after antisense oligonucleotide treatment (ASO) in an animal model of MDS (Sztainberg et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with FOXG1 mutations are currently classified with Rett. However, as these rare FOXG1 mutation patients present with disease from birth and have other symptoms that do not overlap with Rett, a proposal to classify these patients as a separate syndrome was recently submitted (Cutri-French et al, 2020). Therefore, with few exceptions, any discussion about Rett syndrome phenotypes is about how defective MECP2/Mecp2 expression presents in patients and animal models and manifests as a neurodevelopmental disease.…”
Section: Discussionmentioning
confidence: 99%